The Association Between Obesity, Mediterranean Diet Adherence, Zinc, Depression and COVID-19 Susceptibility: An Observational Study - Ozmutaf, Melis; Eren, Fatma Hulyam; Kabaran, Seray (Marmara Univ, Inst Health Sciences, 2024)
Objective: Unhealthy lifestyle factors have been associated with COVID-19 susceptibility, but data for diet and related lifestyle factors are conflicting. The objective of this study was to identify whether obesity, Mediterranean diet, Zn or depression could be associated to the risk of COVID-19 occurrence. Methods: This observational case-control study was conducted in T & uuml;rkiye (between December 2020 - September 2021) with face-toface interview. A total of 100 former COVID-19 subjects as case group and 100 healthy control group, aged 20-54 were included in the study. By semi-structured questionnaire; demographic characteristics and anthropometric measurements was collected. Adherence to the Mediterranean diet was assessed using the Mediterranean Diet Adherence Screener and Mediterranean Diet Score. Daily dietary zinc intake was calculated using a 25-item food frequency questionnaire and blood samples for zinc levels was obtained from each participant. The level of depression was evaluated by Center for Epidemiologic Studies Depression Scale. Results: No differences were found between the anthropometric characteristics of two groups (p>.05). p> .05). Average adherence to the Mediterranean diet were lower in the case groups compared to controls (p<.05). p< .05). While the total zinc intake showed a significant difference between the groups (12.6 +/- 13.0 vs 12.8 +/- 7.2 mg, respectively, p= .003), no difference was observed in the food sources related to zinc intake (9.4 +/- 5.71 vs 10.1 +/- 9.45 mg, p=.052). Case group had significantly lower zinc levels (64.7 +/- 17.6 mu g/dL vs 76.1 +/- 16.7 mu g/dL, p< 0001) in both genders (for male p=.009 and female p< .001, respectively). The majority of case group subjects (76.1 vs 23.8%) had a serum zinc concentration below the reference ranges (p<.001). p< .001). Conclusion: Our findings suggest a negative relationship between Mediterranean diet adherence or serum zinc levels, and COVID-19 occurrence, however further studies are required to examine whether Mediterranean diet consumption or serum zinc status reduces the risk of COVID-19 causally.
Keywords: Mediterranean Diet; zinc; obesity; depression; COVID-19